STRATEGI GURU DALAM MENINGKATKAN MINAT BELAJAR ANAK HIPERAKTIF DI KELAS IIC SEKOLAH DASAR SWASTA IT SHULTONIYAH SAMBAS TAHUN PELAJARAN 2022-2023 - Indah Mutiara Sari; Nuraini Nuraini; Parni Parni (Jurnal Salome : Multidisipliner Keilmuan, 2025)
The purpose of this study is to reveal about: 1). Teachers' learning planning strategies in increasing the learning interest of hyperactive children in the IIC SDS IT Shultoniyah Sambas class for the 2022-2023 Academic Year? 2). Strategies for implementing teacher learning in increasing the learning interest of hyperactive children in the IIC SDS IT Shultoniyah Sambas class for the 2022-2023 Academic Year? 3). Teacher learning evaluation strategies in increasing the learning interest of hyperactive children in the IIC SDS IT Shultoniyah Sambas class for the 2022-2023 Academic Year?. This research technique uses a qualitative approach with a phenomenological research type. Data collection techniques use interviews, observations, and documentation. The data analysis techniques used are data reduction, data presentation, and data inference. The results of the study show that: 1. Teachers' learning planning strategies in increasing the learning interest of hyperactive children in the IIC SDS IT Shultoniyah Sambas class for the 2022-2023 Academic Year, namely, students are always directed to do the 5M, namely observing, asking, trying, concluding and communicating so that the learning process will be easy to do, especially for hyperactive children. 2. Strategies for implementing teacher learning in increasing the learning interest of hyperactive children in the IIC SDS IT Shultoniyah Sambas class for the 2022- 2023 Academic Year, namely, using cooperative learning methods with a scientific approach so that students who are identified as hyperactive are smooth in accepting the learning process provided by the teacher. Teachers also use ice breaking when it is not conducive in class. Usually teachers do singing and playing games. 3. Teacher learning evaluation strategies in increasing the learning interest of hyperactive children in the IIC SDS IT Shultoniyah Sambas class for the 2022- 2023 Academic Year, namely, how to provide KKM standards that are different from normal children. If equalized, it will make it difficult to achieve the learning outcomes of hyperactive children.